Research Orientation to Engineering Education - Modak, J. P. (Journal of Engineering Education Transformations, 2008)
This paper describes the present status of main feature of teaching-learning process i.e. (1) Classroom teaching (2) Deducing there from the present shortcomings of this process (3) subsequently it crystallizes necessary steps to overcome the shortcomings and finally (4) How involvement of a teacher in a research activity helps him in becoming a qualified teacher in a real sense of the term.